FORMULASI DAN EVALUASI EFEKTIVITAS KELEMBABAN SEDIAAN GEL LIDAH BUAYA (ALOE VERA LINN) - Mutiara Syahria; Nurlina, Nurlina; Iskandar Zulkarnain (Yayasan Nusantara Hasana Berdikari, 2026)
Healthy skin is characterized by its balance of moisture, oil, and elasticity, which serve to protect the body from external factors. As we age, skin hydration tends to decrease due to the reduction of natural moisturizing factors (NMF). This study aims to formulate and evaluate the effectiveness and stability of aloe vera gel preparation as a skin moisturizer. Gel preparation formulations were made using carbopol as a base, then evaluated physical properties (organoleptic, viscosity, pH, spreadability, adhesiveness, homogeneity, moisture, syneresis) and testing the effectiveness of skin moisture using a digital skin analyzer. The results showed that the three best formulas and other stability test parameters showed good physical stability. Aloe vera gel preparations (Aloe Vera L) formulated have a stable pH (4.0-7.0) and are safe to be applied to the skin. All three formulas proved to be able to increase skin moisture and maintain the effect for up to 4 hours, with Formula II showing the best percentage of moisture. All preparations also showed good physical stability. Aloe vera gel dosage formulations were successfully made with good physical stability and effective in increasing and maintaining skin moisture.